Regeneration of Adsorbents by the Use of Liquid, Subcritical and Supercritical Carbon Dioxide - Henryk Grajek (Adsorption Science & Technology)
The literature concerning the adsorption and desorption of environmental impurities from adsorbents by means of liquid, subcritical and supercritical carbon dioxide and the author's work on the subject have been reviewed. The influence of the adsorption and desorption temperature, the pressure and the density of the extraction solvent, the solubility of the adsorbate in the extraction solvent, the activation energy for adsorbate desorption and the particle size of the adsorbent on the adsorbate desorption efficiency by this method were discussed.